MELINDUNGI ANAK KORBAN BULLYING DI SEKOLAH (SUATU KAJIAN PEMBAHARUAN HUKUM PIDANA) - Bachtiar Hilmi; Rena Yulia; M. Noor Fajar Al Arif (Universitas Suryakancana, 2022)
Various cases of children who are victims of bullying continue to occur, especially in schools. Children who are victims of bullying suffer psychological harm that causes prolonged trauma and even threatens their lives. Therefore it is important to examine the protection of children who are victims of bullying in schools with a victimological perspective as an effort to reform criminal law. The purpose of this research is to protect children who are victims of bullying by formulating it in legal regulations as a renewal of criminal law. The research method used a normative juridical approach, secondary data sources and literature study data collection techniques. The data were analyzed using a qualitative descriptive method. The results of the study indicate that future criminal law formulations to tackle bullying in schools in the perspective of criminal law renewal are to make special and specific rules related to the crime of bullying both physically and psychologically towards children at school. The stages that can be carried out to be able to overcome bullying cases in the future are First, the formulative policy stage or the legislative policy stage, namely the stage of preparing/formulating criminal law. The second stage, the application policy stage or the judicial/applicative policy stage, is the stage of applying criminal law. And the third stage, the execution policy stage or the executive policy stage, namely the implementation/execution stage of criminal law.Keywords : Legal Protection, Bullying Victims, and Criminal Law Renewal.